"Properties of ethylene-vinyl acetate-glycidyl methacrylate rubber foaming material with double crosslinking system" - ZHAO Yong-jian, SHI Hao-nan, ZHANG Qing-hong, SHI Xin-yan (Hecheng xiangjiao gongye)
With ethylene-vinyl acetate-glycidyl methacrylate (EVM-GMA) rubber as matrix, γ-aminopropyltriethoxysilane (APTES) as grafting monomer and azodicarbonamide as foaming agent, double crosslinked foaming materials were prepared by combination of water crosslinking and peroxide crosslinking. The cell morphology, dynamic mecha-nical properties, and physical and mechanical properties of the foaming materials were investigated by scanning electron microscopy, dynamic mechanical property spectrometer and electronic universal tes-ting machine. The results showed that the double crosslinked foaming process could be realized, and the crosslinking network formed by water crosslin-king could effectively improve the uniformity and dispersion of cell size. When the amount of dicumyl peroxide was 0.25 phr (mass), the double crosslinked foam material had the narrowest cell size distribution, the best foaming effect, and better energy absorption effect, which was suitable for application of damping materials.